PD-1/PD-L Axis in Neuroinflammation: New Insights - Manenti, Susanna; Orrico, Mario; Masciocchi, Stefano; Mandelli, Alessandra; Finardi, Annamaria; Furlan, Roberto (Frontiers in Neurology, 2022)
The approval of immune checkpoint inhibitor (ICIs) by the Food and Drug Administration (FDA) has led to an improvement in the treatment of several types of cancer. The main targets of these drugs are Cytotoxic T-Lymphocyte Antigen 4 (CTLA-4) and Programmed cell death protein-1/Programmed death-ligand-1 pathway (PD-1/PD-L1), important costimulatory molecules for the immune system. Besides being generally safer than common chemotherapy, the use of ICIs has been associated with several immune-related adverse effects (irAEs). Although rare, neurological adverse effects are reported within the irAEs in clinical trials, especially in patients treated with anti-PD-1 antibodies or a combination of both anti-CTLA-4 and PD-1 drugs. The observations obtained from clinical trials suggest that the PD-1 axis may play a remarkable role in the regulation of neuroinflammation and a comprehensive view of these mechanisms is still missing. To date, there is no clear understanding of the role of the PD-1 axis in human neurological disorders, although a plethora of recent studies showed an upregulation of PD-L1 on circulating PBMCs in the persons with multiple sclerosis as compared to healthy controls. Our review aims to summarize the most recent evidence concerning the regulation of neuroinflammation through PD-1 signaling, focusing on cell populations that are involved in this pathway.